AMALGAMATED N P S FERTILIZER ON CROP PERFORMANCE AND NODULATION OF SOYBEAN VARIETIES ON ACIDIC SOIL. - Tesfa Imenu; Tolera Abera; Kinde Lamessa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This experiment was aimed to evaluate the effect of amalgamated NPS chemical fertilizer on crop performance and nodulation of soybean (Glycine max L (Merrill)) varieties on acidic soil during 2020 cropping season. Varieties of soybean i.e “Katta” and “Korme” and six levels of amalgamated NPS chemical fertilizer were used in factorial arrangement within randomized complete block design with three replications. Nodule parameters were highly influenced (P<.001) by the main effect of amalgamated NPS chemical fertilizer levels. The highest grain yield (2390 kg ha-1) was obtained from application of 19(N) 38(P2O) 7(S), kg ha-1 .. “Katta”and “Korme” varieties of soybean were high yielder at level of 19(N) 38(P2O) 7(S), kg ha-1 combined NPS fertilizer application. Therefore, both varieties “Katta” and “Korme” with application of 19(N) 38(P2O) 7(S), kg ha-1 mixed chemical fertilizer were recommended for enhancing nodule development and seeds yield.